THE INFLUENCE OF SHARIA MARKETING MIX ONNDECISIONSPURCHASE IN REVOLUTION 4.0 - Zuriani Hsb, Melisa; Fitria Jayusman, Sri; Munawaroh, Munawaroh; Siregar, Horia (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
This study aims to determine the effect of the Islamic marketing mix on purchasing decisions in the era of revolution 4.0 at the Bintang Bromo Store, Medan. The population in this study were 60 respondents with the determination of the sample using the saturated sample technique. The data analysis technique that the writer uses in this research is descriptive quantitative. The data collection used is by using a questionnaire given to the respondents. The data analysis technique used is simple linear regression, with Y = 9.215 + 0.630 X + e, meaning that the Islamic marketing mix has a significant influence on the purchasing decision variables. The results of the t hypothesis test showed that the value of tcount > ttable = 22,196>1,671. Because the value of tcount is greater than ttable, the hypothesis is accepted. So, it can be concluded that the hypothesis that the variable (X) has been proven or in other words there is a significant effect between the variable (X) on the variable (Y). And based on the coefficient of determination test (R2) of 0.895 or with a percentage of 89.5%, it means that the sharia marketing mix is very influential on purchasing decisions, while the remaining 10.5% is influenced by other variables not examined in the research.